Dermoscopy use by French private practice dermatologists: a nationwide survey. (17th December 2012) - Moulin, C.; Poulalhon, N.; Duru, G.; Debarbieux, S.; Dalle, S.; Thomas, L.
Summary Background Dermoscopy is now recognized as an essential tool for discriminating melanoma from other pigmented lesions, as corroborated by several robust meta‐analyses. Although it is considered to be widely used in European countries, no published data on this topic are available to date, unlike in Australia and the U.S.A. Objectives To describe and quantify the use and learning of dermoscopy among French private practice dermatologists. Methods A questionnaire of 19 items regarding demographic characteristics, dermoscopy use and training, and physician's judgment on dermoscopy was mailed to all French private practice dermatologists. Only questionnaires with an answer to the key item, 'Do you use dermoscopy?' were taken into account. Results Of 3179 mailed questionnaires, 1611 were returned and 1576 were analysable (49·6%). Most respondents declared using dermoscopy (94·6%), using their dermoscope several times a day (82·7%) and/or for the diagnosis of nonpigmented lesions (87·7%). Physicians learned dermoscopy mainly through books (75·8%) and/or conferences (88·6%); 12·8% reported a dedicated university degree. Dermoscopy helps to detect melanoma earlier and to perform fewer biopsies according to 86·6% and 74·6%, respectively. On multivariate analysis, female sex and age under 45 years were significantly associated with higher utilization rate of dermoscopy [odds ratio 1·89, 95% confidence interval (CI) 1·15–3·10; and 2·85, 95% CI 1·14–7·11, respectively]. Conclusions This is the first published nationwide survey of dermoscopy practice in Europe. Despite potential classification and/or selection bias, the particularly high penetration rate found in our study suggests that dermoscopy is now widely accepted by French private practice dermatologists for the routine management of both pigmented and nonpigmented lesions.